2016
DOI: 10.3847/2041-8205/827/1/l2
|View full text |Cite
|
Sign up to set email alerts
|

Strong Evidence for the Density-Wave Theory of Spiral Structure in Disk Galaxies

Abstract: The density-wave theory of galactic spiral-arm structure makes a striking prediction that the pitch angle of spiral arms should vary with the wavelength of the galaxy's image. The reason is that stars are born in the density wave but move out of it as they age. They move ahead of the density wave inside the co-rotation radius, and fall behind outside of it, resulting in a tighter pitch angle at wavelengths that image stars (optical and near infrared) than those that are associated with star formation (far infr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
44
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 52 publications
(54 citation statements)
references
References 22 publications
9
44
1
Order By: Relevance
“…Thus, the star-forming arm is upstream from the blue arm, which is in turn upstream from the red arm. This conforms with the density-wave theory's prediction of variation in pitch angle with the image wavelength of light (Pour-Imani et al 2016). clouds before they actually crossed the maximum of the spiral potential. Although such a possibility cannot be ruled out, it does not seem to be reflected in most simulations of galactic density waves.…”
Section: Introductionsupporting
confidence: 88%
See 3 more Smart Citations
“…Thus, the star-forming arm is upstream from the blue arm, which is in turn upstream from the red arm. This conforms with the density-wave theory's prediction of variation in pitch angle with the image wavelength of light (Pour-Imani et al 2016). clouds before they actually crossed the maximum of the spiral potential. Although such a possibility cannot be ruled out, it does not seem to be reflected in most simulations of galactic density waves.…”
Section: Introductionsupporting
confidence: 88%
“…This issue is relevant to the current paper because it has been argued that failure to find consistent downstream displacements of observational tracers of star formation and stars of different ages is an argument against the reality of long-lasting spiral arms (Foyle et al 2011). By contrast, in previous work (Pour-Imani et al 2016) we confirmed a key prediction of the densitywave theory, that spiral-arm pitch angle varies with observation wavelength. This is in contrast to the predictions of rival theories, such as the Manifold theory (for a discussion of this theory test see Athanassoula et al 2010).…”
Section: Introductionsupporting
confidence: 54%
See 2 more Smart Citations
“…From the measurements of such offsets as a function of galactocentric radius, the pattern speed of the density wave can be calculated (Egusa et al 2004;Louie et al 2013). This effect causes the pitch angle of spirals to vary with wavelength, which is indeed seen in several galaxies (Pour-Imani et al 2016 On the other hand, if spiral arms were formed due to density inhomogeneities, offsets would not occur, or they would be small and would not have a regular distribution (Grand et al 2012b,a;D'Onghia et al 2013;Baba et al 2015;Choi et al 2015). Thus, if no offsets are seen between the distributions of molecular gas and young stars, we may conclude that star formation in the compressed gas has occurred rather fast (see Egusa et al 2009), or that even the classical density wave theory cannot explain spiral structure formation (Foyle et al 2011).…”
Section: Introductionmentioning
confidence: 81%